Fracture behavior of thermally aged Ag–Cu composite sinter joint through microscale tensile test coupled with nano X-ray computed tomography - Tomoki Matsuda (Materials & Design, 2021)
Herein, we investigated the fracture behavior of thermally aged Ag–Cu composite sinter joints through nano-X-ray computed tomography (nano-CT) combined with microscale tensile testing. Nano-CT results showed that the joint comprised Ag/oxidized Cu flake sintered layer and Cu oxide, which was formed on the Cu substrate; further, pores were present at the interface between the substrate and Cu oxide layer. The tensile test showed that the stress increased with plastic deformation up to a maximum of 308 MPa, before a subsequent steep decrease due to crack initiation inside the sintered layer. The nano-CT and in situ observation results suggest that the microscale joint fractured through the interface between the oxidized Cu flake and Ag. Results obtained herein suggest that microscale tensile testing coupled with nano-CT is an effective approach to describe the intrinsic fracture behavior of joints.